1955
DOI: 10.1107/s0365110x55000947
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nuclear radiation on the structure of zircon

Abstract: The effect of nuclear radiation from the decay of uranium, thorium and their daughter elements on the specific gravity, unit-cell dimensions, and optical properties of zircon has been studied. During the course of the irradiation the specific gravity of zircon drops 16 %, the material becomes isotropic and so disordered as to fail to yield recognizable X-ray diffraction peaks. It is proposed that the observed effects are predominantly due to the displacement of atoms by recoil nuclei and by high temperatures g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
217
1

Year Published

1963
1963
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(228 citation statements)
references
References 1 publication
10
217
1
Order By: Relevance
“…A very slight suggestion of asymmetry toward lower 20 values is the only indication of peak broadening. The multiple solutions for cell dimensions agreed within the indicated limits of error in Holland and Gottfried (1955) or Fairbairn and Hurley (1957), the c 0 value indicates a modest radiation dosage of about 1.0 X 10 15 a-particles/ mg.…”
Section: Physical Properties Of the Zircon Concentratesmentioning
confidence: 99%
See 1 more Smart Citation
“…A very slight suggestion of asymmetry toward lower 20 values is the only indication of peak broadening. The multiple solutions for cell dimensions agreed within the indicated limits of error in Holland and Gottfried (1955) or Fairbairn and Hurley (1957), the c 0 value indicates a modest radiation dosage of about 1.0 X 10 15 a-particles/ mg.…”
Section: Physical Properties Of the Zircon Concentratesmentioning
confidence: 99%
“…Surprisingly, the X-ray and index of refraction measurements have shown that the L-312 zircons now display the radiation damage to be expected in a young rock perhaps 100 million years old (Holland and Gottfried, 1955;Fairbairn and Hurley, 1957). Apparently, annealing of the zircon structure accompanied or followed the disturbance of the contained lead-uranium systems.…”
Section: Evidence On the Nature Of The Disturbance Mechanismsmentioning
confidence: 99%
“…. ) are known to undergo amorphization as a consequence of the α-decay of radionuclide impurities (typically 238 U, 235 U and 232 Th and their decay products) (Holland and Gottfried 1955, Lumpkin and Ewing 1988, Ewing 1994, Weber et al 1994. Due to the properties (mainly chemical durability) that some of these materials offer as waste forms for the immobilization of high-level waste and plutonium (Weber et al 1998, Ewing 1999, natural materials and their synthetic equivalents have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…At this first stage, sharp Bragg maxima are observed that decrease in intensity with increasing radiation dose. The crystalline matrix is expanded (as shown by the unit-cell swelling (Holland andGottfried 1955, Murakami et al 1991)) as a consequence of the shear deformation produced by the localized defects created by α-particles (Ríos and Salje 1999). At intermediate doses the decrease of the intensity of diffraction maxima and their broadening is accompanied by the appearance of two diffuse rings, as observed from electron diffraction images: in natural (Murakami et al 1991, Capitani et al 2000 and irradiated zircon Ewing 1992b, Weber et al 1994) samples, pyrochlores (Lumpkin and Ewing 1988) and Cm-doped Ca 2 Nd 8 (SiO 4 )O 2 (Weber 1993), for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation